Facile fabrication of flower-like Ni-Co-Mn based LDHs and their superior catalytic performance for atenolol, nitrite and methanol. Issue 6 (December 2022) - Lee, Min-Guk; Govindan, Kadarkarai; Radhakrishnan, Sivaprakasam; Ko, Tae Hoon; Kim, Byoung-Suhk
Abstract: In this work, flower-like ternary nickel-cobalt-manganese hydroxide (NiCoMn-OH; NCM) was synthesized through a simple chemical bath deposition in presence of ammonium persulfate (APS) as a catalyst at low temperature. The structures and morphologies of the prepared materials were studied by various analytical methods. The mechanism for the formation of NCM flower-like nanostructure was investigated in detail by various optimization studies. The prepared materials were used for the tri-functional applications including catalytic atenolol (ATL) degradation, electrocatalytic oxidation of methanol and nitrite. The NCM catalyzed peroxomonosulfate (PMS) activation for ATL degradation was investigated. Moreover, when the NCM was used as an electrocatalyst for methanol electrooxidation, the NCM electrode exhibited an excellent catalytic rate constant (0.223 × 10 4 cm 3 .mol −1 .s −1 ) and long-term stability. Further, as an electro-catalyst for nitrite electro-oxidation, the NCM exhibited good sensitivity (532 μA μM −1 cm −2 ), detection limit (1.0 μM (S/N = 3)), and wide linear range (up to 8.3 mM). Graphical Abstract: ga1 Highlights: Green synthesis of flower-like NiCoMn hydroxide (NCM) nanostructure. The mechanism for the formation of flower structured studied in details NCM exhibited excellent catalytic behavior for atenolol degradation. NCM demonstrated good electrocatalytic properties for methanol and nitrite.